2016
DOI: 10.1080/13662716.2016.1156519
|View full text |Cite
|
Sign up to set email alerts
|

Adoption readiness in service innovation: the case of digital money

Abstract: One challenge for firms seeking to develop new services is to understand the conditions likely to affect rates of adoption. Understanding relative degrees of "adoption readiness" provides innovators with information to choose market segments and indicates opportunities to influence adoption environments. This paper considers these issues through the case of digital money, a service innovation some claim to have the potential to provide major economic and social benefits. However, there is little research into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 56 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…For example, vulnerable customers may easily be targeted by merchants because of the everyday monitoring of their financial behaviour on the internet (Larsson et al, 2016) and obligatory acceptance of cookies may lead to unwanted tracking on bank websites (Yu et al, 2016). Taken together, privacy is among the most-discussed risks on the road to the full adoption of DPMs by various groups of bank customers (B atiz-Lazo et al, 2014;Larsson et al, 2016;Lundberg et al, 2014;Rehncrona, 2018;Thomas et al, 2016;Zhang et al, 2018).…”
Section: Bank Customers' Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, vulnerable customers may easily be targeted by merchants because of the everyday monitoring of their financial behaviour on the internet (Larsson et al, 2016) and obligatory acceptance of cookies may lead to unwanted tracking on bank websites (Yu et al, 2016). Taken together, privacy is among the most-discussed risks on the road to the full adoption of DPMs by various groups of bank customers (B atiz-Lazo et al, 2014;Larsson et al, 2016;Lundberg et al, 2014;Rehncrona, 2018;Thomas et al, 2016;Zhang et al, 2018).…”
Section: Bank Customers' Intentionmentioning
confidence: 99%
“…However, many customers perceive mobile payments as too easy to access and conduct and security is perceived to decrease when customers can use their money in a fast and easy way without any additional effort (Rehncrona, 2018). Based on previous research (Dahlberg et al, 2015;Larsson et al, 2016;Thomas et al, 2016;Shin, 2021), security is identified as a significant risk in the digital payment process and Lian and Yen (2013) indicated that even adopters perceive security as a major risk because of the potential risk that data can be stolen and misused. Despite ongoing technical improvements, mobile payments are perceived as insecure (Rehncrona, 2018;Shankar et al, 2020).…”
Section: Bank Customers' Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2015). These developments have influenced the banking and commerce industries as well as customers’ readiness to adopt new digital services (Thomas et al. , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Societal developments have made citizens more technology dependent (Priporas et al, 2017), rapidly challenging their behavior (Yang et al, 2015). These developments have influenced the banking and commerce industries as well as customers' readiness to adopt new digital services (Thomas et al, 2016). In fact, the adoption of digital payment methods (DPMs) has increased worldwide, and cash usage has further decreased due to the COVID-19 pandemic, forcing a move from traditional to digital services (Leong et al, 2022;Santo and Marques, 2022).…”
Section: Introductionmentioning
confidence: 99%